Water Quality Survey of Streams from Retezat Mountains (Romania) - Pascariu, Mihai-Cosmin; Tulucan, Tiberiu; Niculescu, Mircea; Sebarchievici, Iuliana; Ștefănuț, Mariana Nela (Journal of Environmental Geography, 2016)
The Retezat Mountains, located in the Southern Carpathians, are one of the highest massifs in Romania and home of the Retezat National Park, which possesses an important biological value. This study aimed at the investigation of water quality in creeks of the Southern Retezat (Piule-Iorgovanul Mountains) in order to provide information on pollutants of both natural and anthropogenic origin, which could pose a threat for the human health. Heavy metal and other inorganic ion contents of samples were analyzed with on-site and laboratory measurements to estimate water quality. The samples were investigated using microwave plasma - atomic emission spectrometry to quantify specific elements, namely aluminium, cadmium, cobalt, chromium, copper, iron, magnesium, manganese, molybdenum, nickel, lead and zinc. The results were compared with the European Union and Romanian standards regarding drinking water and surface water quality. The studied heavy metals have been found to be in very low concentrations or under the method’s detection limit. Thus, in the microbasin corresponding to the sampling points, there seems to be no heavy metal pollution and, from this point of view, the samples comply as drinking water according to the European Union and Romanian recommendations. Our findings confirm that the Retezat Mountains are still among the least contaminated regions in Europe and that the ecosystem and the human health is not negatively influenced by water quality problems.